Harmony of Grobner Bases and the Modern Industrial Society : the Second Crest-sbm International Conference. - Hibi, Takayuki (World Scientific, 2012)
This volume consists of research papers and expository survey articles presented by the invited speakers of the conference on "Harmony of Gröbner Bases and the Modern Industrial Society". Topics include computational commutative algebra, algebraic statistics, algorithms of D-modules and combinatorics. This volume also provides current trends on Gröbner bases and will stimulate further development of many research areas surrounding Gröbner bases.